Voices of women living with FASD: Perspectives on promising approaches in substance use treatment, programs and care - Rutman, Deborah (First Peoples Child & Family Review, 2013)
Research and practice wisdom tells us that women who themselves have FASD are at high risk of having concurrent substance use and mental health problems, and of having a baby with FASD. Despite this, there is a dearth of published information that has focused on the support needs of women with FASD who have substance use problems, or on effective practice in providing substance use treatment and care for women with FASD.This article presents findings based on interviews with 13 substance-using women with FASD, which was a key facet of a three-year research project that had three inter-related components. The research also included a review of the literature regarding promising approaches to substance use treatment and care with women with FASD and interviews with multl-disciplinary service providers across British Columbia to identify promising and innovative programs, resources and approaches relating to substance use treatment for women with FASD. Highlighted are promising approaches and good practice and/or programs for women with FASD who have addictions problems, from the perspective of individuals most directly affected by the issues: women with FASD who have substance use problems.